Endoscopic retrograde appendicitis therapy for acute appendicitis: a systematic review and meta-analysis - Dhindsa, Banreet; Naga, Yassin; Praus, Alexander; Saghir, Syed Mohsin; Mashiana, Harmeet; Ramai, Daryl; Chandan, Saurabh; Sayles, Harlan; Dhaliwal, Amaninder; Bhat, Ishfaq; Singh, Shailender; Adler, Douglas (Endoscopy International Open, 2022)
Background and study aims Endoscopic retrograde appendicitis therapy (ERAT) is an endoscopic procedure for management of patients with acute appendicitis (AA). In addition to being minimally invasive, it has the added advantages of preservation of appendix and simultaneous inspection of colon. We performed a systematic review and meta-analysis on ERAT in patients with AA.Methods We conducted a comprehensive search of multiple electronic databases (from inception through January 2022) to identify studies reporting ERAT in AA. The primary outcome was to evaluate the overall clinical and technical success of ERAT. The secondary outcome was to study the total and individual adverse events (AEs). The meta-analysis was performed using Der Simonian and Laird random effect model.Results Seven studies reporting on 298 patients were included. The majority of the patient population was male (55.3 %), with mean age of 31 ± 12.39 years. The pooled technical success rate was 99.36 % (95 % CI 97.61–100, I2 = 0) and the pooled clinical success rate was 99.29 % (95 % CI 97.48–100, I2 = 0). The pooled AE rate was 0.19 % (95 % CI 0–1.55, I2 = 0). The most common AE was perforation with 0.19 % (95 % CI 0–1.55, I2 = 0). The recurrence rate was 6.01 % (95 % CI 2.9–9.93, I2 = 20.10). Average length of procedure was 41.1 ± 7.16 min. Low heterogeneity was noted in in our meta-analysis.Conclusions ERAT is a safe procedure with high rates of clinical and technical success in patients with AA. Further randomized controlled trials should be performed to assess the utility of ERAT in AA as compared to laparoscopic appendectomy.